Triarylamine‐Pyridine‐Carbonitriles for Organic Light‐Emitting Devices with EQE Nearly 40 - Chen, Yi‐Kuan; Jayakumar, Jayachandran; Hsieh, Chia‐Min; Wu, Tien‐Lin; Liao, Chun‐Cheng; Pandidurai, Jayabalan; Ko, Chang‐Lun; Hung, Wen‐Yi; Cheng, Chien‐Hong (Advanced materials (Weinheim), 2021)
Highly efficient thermally activated delayed fluorescence (TADF) molecules are in urgent demand for solid‐state lighting and full‐color displays. Here, the design and synthesis of three triarylamine‐pyridine‐carbonitrile‐based TADF compounds, TPAPPC, TPAmPPC, and tTPAmPPC, are shown. They exhibit excellent photoluminescence quantum yields of 79−100% with small ΔEST values, fast reverse intersystem crossing (RISC), and high horizontal dipole ratios (Θ// = 86−88%) in the thin films leading to the enhancement of device light outcoupling. Consequently, a green organic light‐emitting diode (OLED) based on TPAmPPC shows a high average external quantum efficiency of 38.8 ± 0.6%, a current efficiency of 130.1 ± 2.1 cd A–1, and a power efficiency of 136.3 ± 2.2 lm W–1. The highest device efficiency of 39.8% appears to be record‐breaking among TADF‐based OLEDs to date. In addition, the TPAmPPC‐based device shows superior operation lifetime and high‐temperature resistance. It is worth noting that the TPA‐PPC‐based materials have excellent optical properties and the potential for making them strong candidates for TADF practical application. Three 2,6‐diphenylpyridine‐3,5‐dicarbonitrile‐based compounds with excellent photoluminescent quantum yields (79–100%) and high horizontal dipole ratios (86−88%) in the thin films are demonstrated. With two methyl groups on the triarylamines, the spin−orbit coupling is enhanced due to the elevated locally excited triplet states (3LE), leading to a fast reverse intersystem crossing. Green thermally activated delayed fluorescence (TADF) organic light‐emitting diodes based on them exhibit a record‐high external quantum efficiency of 39.8% without any optical extraction technique.